Genetic Diversity of NHE1, Receptor for Subgroup J Avian Leukosis Virus, in Domestic Chicken and Wild Anseriform Species - Reinišová, Markéta; Plachý, Jiří; Kučerová, Dana; Šenigl, Filip; Vinkler, Michal; Hejnar, Jiří (PloS one, 2016)
J subgroup avian leukosis virus (ALV-J) infects domestic chicken, jungle fowl, and turkey and enters the host cell through a receptor encoded by tvj locus and identified as Na+/H+ exchanger 1 (NHE1). The resistance to ALV-J in a great majority of examined galliform species was explained by deletions or substitutions of the critical tryptophan 38 in the first extracellular loop of NHE1, and genetic polymorphisms around this site predict the susceptibility or resistance of a given species or individual. In this study, we examined the NHE1 polymorphism in domestic chicken breeds and documented quantitative differences in their susceptibility to ALV-J in vitro. In a panel of chicken breeds assembled with the aim to cover the maximum variability encountered in domestic chickens, we found a completely uniform sequence of NHE1 extracellular loop 1 (ECL1) without any source of genetic variation for the selection of ALV-J-resistant poultry. In parallel, we studied the natural polymorphisms of NHE1 in wild ducks and geese because of recent reports on ALV-J positivity in feral Asian species. In anseriform species, we demonstrate a specific and highly conserved critical ECL1 sequence without any homologue of tryptophan 38 in accordance with the resistance of duck cells to prototype ALV-J. Last, we demonstrated that the new Asian strains of ALV-J have not evolved their envelope glycoprotein to the entry the duck cells. Our results contribute substantially to the current discussion of possible heterotransmission of ALV-J and its spill-over into the wild ducks and geese.
Keywords: kur domácí; genetická variace; Chickens; Animals, Wild; Sequence Homology, Amino Acid; molekulární sekvence - údaje; Amino Acid Sequence; divoká zvířata; sekvenční homologie aminokyselin; Sodium-Hydrogen Exchangers; kultivované buňky; Animals; hospodářská zvířata; kuřecí embryo; Animals, Domestic; zvířata; sekvence aminokyselin; Cells, Cultured; Molecular Sequence Data; Genetic Variation; Na(+)-H(+) antiport; Chick Embryo